Pomoże ktoś?

Rozwiąż równania:

a) 3x - 2 = 1/2 * x + 3

b) 2x - 4 = 1/3 * x - 2

x = x/2 + x/3 - 2

d) 8y - 3 = (11y - 1)/2

e) x - (x - 3)/3 = 3 + 2x

x/3 = (x - 2)/5

8) (z + 3)/2 - (z - 4)/3 = 0

b) (x - 6)/4 + x = 1/2 * (x - 3) + 1/4 * x h)

(2 + x)/3 + (3 - x)/6 = 1

3/4 * x - (x + 1)/2 = x - 3/4

k) - (x - 3)/3 - 1 = - x/3 - 2

1) (x + 1)/2 - x/3 = 1

}) (x + 2)/3 - (x - 2)/2 = 1 - x

m) y/2 - (3y)/4 + (5y)/6 = y - 1

n) - (2x + 5)/6 + (5(x - 2))/4 - (2(2x + 1))/3 = 1

o) (3n - 1)/9 - (n - 2)/8 = 1/2